Effects of mercapto-palygorskite on Cd distribution in soil aggregates and Cd accumulation by wheat in Cd contaminated alkaline soil. (May 2021) - Wang, Yale; Xu, Yingming; Liang, Xuefeng; Sun, Yuebing; Huang, Qingqing; Qin, Xu; Zhao, Lijie
Abstract: Cadmium (Cd) contamination in alkaline soils is a serious issue in China. As the basic structural units of soil, soil aggregates play an important role in the migration and transformation of heavy metal. However, there are few studies on the effects of adding amendments on Cd distribution in soil aggregates in alkaline soils. In this study, pot experiments were conducted to assess the effects of mercapto-palygorskite (MPAL) on soil aggregates and Cd accumulation in wheat. The results showed that MPAL application had no effect on wheat yield but significantly reduced the Cd uptake by the roots and the Cd transport to the adjacent internode. Application of 0.1% MPAL reduced the Cd concentration in two wheat grains (0.57 and 0.44 mg/kg, control) to 0.10 and 0.09 mg/kg in moderately Cd-contaminated soil, which are below the China national standard limit of 0.1 mg/kg (GB 2762-2017). MPAL application had no effect on soil pH, cation exchange capacity, mass proportion and mean weight diameter of soil aggregates, but increased soil organic matter content. Importantly, MPAL application promoted the migration of Cd from large particles (>0.25 mm) to small particles (<0.048 mm), reduced the unstable Cd fractions in >0.25 mm soil particles of clay soil and in >0.075 mm soil particles of sandy soil, and increased the stable Cd fractions in bulk soils and soil aggregates. The effects of MPAL addition on soil aggregates (grain size fraction metals loading and accumulation factor) of sandy soil were more prominent than on those of clay soil. Under MPAL treatments, wheat grains Cd concentration was significantly positively correlated with the available Cd in >0.075 mm soil particles and the total Cd in >0.25 mm soil particles. These results indicated that MPAL application in alkaline soils promoted the migration of Cd to micro-aggregates and inhibited the uptake and transport of Cd by wheat roots, thus reducing the Cd concentration in wheat grains. Graphical abstract: Mercapto-palygorskite (MPAL) could promote the migration of Cd from macro-aggregates to micro-aggregates and decrease the available Cd content in macro-aggregates and bulk soils. Meanwhile, MPAL changed the Cd fractions by increasing the stable Cd fractions and decreasing the unstable Cd fractions in bulk soil and soil aggregates. Under the treatment of MPAL, the Cd uptake and transport capacity of wheat roots decreased significantly. Thus, MPAL could ensure the safety of wheat grain in lightly to moderately Cd contaminated alkaline soil. Image 1 Highlights: Mercapto-palygorskite was an efficient material for Cd contaminated alkaline soil. Mercapto-palygorskite promoted the migration of Cd to micro-aggregates. Mercapto-palygorskite reduced available Cd content in macro-aggregates and bulk soil. Mercapto-palygorskite decreased Cd uptake and transport to internode by wheat roots.